Design and implementation of half-space radiation high frequency broadband "spherical" transducer based on anti-sound baffle and circuit matching. (January 2022) - Zhao, Hui; Li, Haisen; Wang, Yan; Liu, Zhenjun; Bian, Jiacong; Zhou, Tian
Abstract: In underwater acoustic communication engineering applications, it is sometimes necessary to place the communication transducers underwater. This usually requires the transducers to have the ability to radiate in half-space. At the same time, in order to reduce the transmission error rate, it is also necessary that the transducers have the ability to operate in a wide band. The spherical piezoelectric transducers have full space radiation, and high power and energy density. The design of spherical transducer by using anti-sound baffle and circuit tuning can meet the requirements of underwater communication transducers. In this work, we analyze the directivity of a spherical transducer by comparing the simulations and theoretical computations. In addition, the broadband performance of a spherical transducer is analyzed based on series inductance tuning. Finally, a half-space broadband spherical transducer prototype is manufactured and its performance is tested and verified by performing experiments. The experimental results show that the bandwidth of the spherical transducer can be increased by series inductance. Moreover, the results show that the distance from the center of the spherical transducer to the anti-sound baffle and the working frequency have a significant effect on the directivity of a spherical transducer. The test results of transducer prototype show that the directivity angle of the transducer is greater than 180°, and the operating bandwidth is around 18 kHz–54 kHz.